The microhardness measurement and polarized light microscopic evaluation for enamel surface after debonding of brackets using different orthodontic adhesive materials (A comparative in vitro study) (Mustansiria Dental Journal, 2004)
This study was carried out to compare the effects of different orthodontic adhesive materials on the micro-hardness of human enamel surface with different incubation period and ot evaluate the morphology of enamel surface before and after orthodontic treatment using polarized light microscope. The sample includes one hundred twenty sound maxillary arid mandibular first premolar teeth which have been extracted for orthodontic treatment purpose from (13- 19) years old patients. The samples were divided into one as a control group and three experimental groups (lIl.Ill) according to the type of the orthodontic adhesive materials Reliance orthodontic products No-Mix. Advantage No-Mix. Orthodontic bonding system No-Mix) respectively. Each group consists of 03 samples and each group subdivided into three subgroups (10 sample) according ot the time of incubation 2( weeks,4 weeks and 8 weeks) and each subgroup divided to (5 upper, 5 lower). The study showed that enamel decalcification was associated with fixed orthodontic appliance thereby and the hardness of enamel si highest with group I (orthodontic bonding system No-Mix) folowed by group 1(Reliance orthodontic products) and group I (Advantage No-Mix). The study indicate that there was non significant difference between group I (Advantage No-Mix and group I (Orthodontic bonding system No-Mix) after 2 and 4 weeks period times bonding ni reduction of micro hardness values in both upper and lower teeth-while there si high significant difference between them ni micro hardness values after 8weks period times bonding ni both upper and lower teeth. The result of polarized light microscope finding show destruction of the perikymata of enamel during 2 weeks period time and increased ni destruction during 4 weeks period time but during 8 weeks period time there is remineralization only ni group 1 fOrthodontic bonding system No-Mix)